Demography, maternal health and the epidemiology of malaria and other major infectious diseases in the rural department Tsamba-Magotsi, Ngounie Province, in central African Gabon. (December 2017) - Manego, R.; Mombo-Ngoma, G.; Witte, M.; Held, J.; Gmeiner, M.; Gebru, T.; Tazemda, B.; Mischlinger, J.; Groger, M.; Lell, B.; Adegnika, A.; Agnandji, S.; et al.
Abstract Background Sub-Saharan Africa is undergoing an epidemiological transition from a predominance of infectious diseases to non-communicable and lifestyle related conditions. However, the pace of this transition and the pattern of disease epidemiology are uneven between affluent urban and rural poor populations. To address this question for a remote rural region located in the central African rainforest region of Gabon, this study was conducted to assess reasons for health care attendance and to characterize the epidemiology of malaria and other major infectious diseases for the department of Tsamba Magotsi. Methods Major causes for health care attendance were collected from local hospital records. Cross sectional population based surveys were performed for the assessment of local malaria epidemiology. Pregnant women attending antenatal care services were surveyed as a sentinel population for the characterization of chronic viral and parasitic infections in the community. Results Infectious diseases were responsible for 71% (7469) of a total of 10, 580 consultations at the formal health care sector in 2010. Overall, malaria – defined by clinical syndrome – remained the most frequent cause for health care attendance. A cross sectional malaria survey in 840 asymptomatic individuals residing in Tsamba Magotsi resulted in aPlasmodium spp. infection prevalence of 37%. The infection rate in 2–10 year old asymptomatic children – a standard measure for malaria endemicity – was 46% (100 of 217) withP. falciparum as predominant species (79%). Infection with other plasmodial species (P. ovale andP. malariae ) presented most commonly as coinfections (23.2%). Prevalence of HIV, HBV, and syphilis were 6.2, 7.3, and 2.5%, respectively, in cross-sectional assessments of antenatal care visits of pregnant women. Urogenital schistosomiasis and the filarial pathogensLoa loa andMansonella perstans are highly prevalent chronic parasitic infections affecting the local population. Conclusions Despite major improvements in the accessibility of Tsamba Magotsi over the past decade the epidemiological transition does not appear to have majorly changed on the spectrum of diseases in this rural Gabonese population. The high prevalence ofPlasmodium infection indicates a high burden of malaria related morbidity. Infectious diseases remain one of the most important health issues and further research activities in the field of tropical medicine and infectious diseases could help improve health care for the local population.